Effect of topical ketorolac 0.4%, nepafenac 0.1%, and bromfenac 0.09% on postoperative inflammation using laser flare photometry in patients having phacoemulsification. Issue 10 (October 2015) - Sahu, Sabin; Ram, Jagat; Bansal, Reema; Pandav, Surinder S.; Gupta, Amod
Abstract : Purpose : To study the effect of topical ketorolac 0.4% (Acular LS), bromfenac 0.09% (Megabrom), and nepafenac 0.1% (Nevanac) on postoperative inflammation using laser flare photometry in patients having phacoemulsification with posterior chamber intraocular lens (PC IOL) implantation. Setting : Tertiary care center, Chandigarh, India. Design : Prospective randomized case series. Methods : Patients with age‐related cataract having phacoemulsification with PC IOL implantation were randomized into 4 groups receiving topical ketorolac 0.4% (Group A), bromfenac 0.09% (Group B), nepafenac 0.1% (Group C), or no nonsteroidal antiinflammatory drugs (NSAIDs) (Group D, control). The topical NSAIDs were started 1 day prior to the surgery and continued for 6 weeks postoperatively. All patients received a standard regimen of moxifloxacin 0.5% (Vigamox) and prednisolone acetate 1.0% (Pred Forte) eyedrops in tapering doses postoperatively. Visual acuity, intraocular pressure (IOP), laser flare photometry, and fundus examination were done preoperatively and postoperatively at 1 day and 1, 2, 4, and 8 weeks. Results : The study comprised 120 patients (120 eyes) (Group A = 33 patients, Group B = 30 patients, Group C = 31 patients, and Group D = 26 patients). The laser flare photometry values at the end of 4 weeks and 8 weeks were minimal in the nepafenac group compared with the other NSAID groups and the no‐NSAID group ( P = .032 at 4 weeks and P = .252 at 8 weeks). Conclusions : The topical NSAIDs ketorolac 0.4%, bromfenac 0.09%, and nepafenac 0.1% were effective for the reduction of postoperative inflammation following phacoemulsification. Compared with ketorolac tromethamine, bromfenac, and the control, nepafenac was significantly effective 1 month postoperatively in reducing anterior chamber flare, as evidenced by decreased laser flare photometry. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.